Cigarette Smoke Inhibits Recruitment of Bone-Marrow-Derived Stem cells to The Uterus - Zhou, Yuping (2010)
Cigarette smoking leads to female infertility and a decreased incidence of endometriosis. Bone marrow derived stem cells are recruited to uterine endometrium and endometriosis. The effect of cigarette smoking on stem cell recruitment to any organ is uncharacterized. We hypothesized that bone marrow-derived mesenchymal stem cell recruitment to the uterus and differentiation would be diminished by cigarette smoke. We used human mesenchymal stem cells (hMSC) in vitro and a mouse model of cigarette smoke exposure. After myeloablation female C57BL/6J received bone marrow cells from males. Mice were exposed to room air or smoke from unfiltered cigarettes. Immunofluorescence and Y-FISH was performed on uterine sections. In vitro hMSCs were treated with 8-Br-cAMP to induce endometrial cell differentiation with or without cigarette smoke extract (CSE) and decidualization assessed morphologically and by prolactin expression. After 4 weeks the total number of Y-chromosome cells in the uterus was reduced by 68% in the smoke exposed mice. Both leukocytes and bone marrow derived endometrial cells were reduced by 60% and 73%, respectively. Differentiation of bone marrow derived cell to endometrial epithelial cells was reduced by 84%. hMSC treated with CSE failed to show cytological characteristics of decidualization. mRNA levels of the decidualization marker prolactin were decreased by 90% in CSE treated cells. Smoking inhibits both recruitment of bone marrow derived stem cells to uterus and stem cell differentiation. Inhibition of stem cells recruitment may be a general mechanism by which smoking leads to long term organ damage through inability to repair or regenerate multiple tissues.